Transcriptome Analysis of Calcium- and Hormone-Related Gene Expressions during Different Stages of Peanut Pod Development - Li, Yan; Meng, Jingjing; Yang, Sha; Guo, Feng; Zhang, Jialei; Geng, Yun; Cui, Li; Wan, Shubo; Li, Xinguo (Frontiers in Plant Science, 2017)
Peanut is one of the calciphilous plants. Calcium serves as a ubiquitous central hub in a large number of signaling pathways. In the field, free calcium ion (Ca2+)-deficient soil can result in unfilled pods. Four pod stages were analyzed to determine the relationship between Ca2+ excretion and pod development. Peanut shells showed Ca2+ excretion at all four stages; however, both the embryo of Stage 4 (S4) and the red skin of Stage 3 (S3) showed Ca2+ absorbance. These results showed that embryo and red skin of peanut need Ca2+ during development. In order to survey the relationship among calcium, hormone and seed development from gene perspective, we further analyzed the seed transcriptome at Stage 2 (S2), S3, and S4. About 70 million high quality clean reads were generated, which were assembled into 58,147 unigenes. By comparing these three stages, total 4,457 differentially expressed genes were identified. In these genes, 53 Ca2+ related genes, 40 auxin related genes, 15 gibberellin genes, 20 ethylene related genes, 2 abscisic acid related genes, and 7 cytokinin related genes were identified. Additionally, a part of them were validated by qRT-PCR. Most of their expressions changed during the pod development. Since some reports showed that Ca2+ signal transduction pathway is involved in hormone regulation pathway, these results implied that peanut seed development might be regulated by the collaboration of Ca2+ signal transduction pathway and hormone regulation pathway.